2013
DOI: 10.1111/cei.12148
|View full text |Cite
|
Sign up to set email alerts
|

Glucose impairs B-1 cell function in diabetes

Abstract: SummaryB-1 lymphocytes produce natural immunoglobulin (Ig)M, among which a large proportion is directed against apoptotic cells and altered self-antigens, such as modified low-density lipoprotein (LDL). Thereby, natural IgM maintains homeostasis in the body and is also protective against atherosclerosis. Diabetic patients have an increased risk of developing certain infections as well as atherosclerosis compared with healthy subjects, but the underlying reason is not known. The aim of this study was to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 39 publications
1
33
0
Order By: Relevance
“…This study reveals a novel role for B-1a cells in modulating glucose intolerance in opposition to pathogenic B-2 cells. Consistent with a previous report ( 33 ), we observed that the HFD resulted in a decreased frequency of B-1a cells in the PerC and VAT but not in the spleen. At the same time, total B cells and B-2 cells increased in the VAT, in agreement with our previous findings ( 16 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This study reveals a novel role for B-1a cells in modulating glucose intolerance in opposition to pathogenic B-2 cells. Consistent with a previous report ( 33 ), we observed that the HFD resulted in a decreased frequency of B-1a cells in the PerC and VAT but not in the spleen. At the same time, total B cells and B-2 cells increased in the VAT, in agreement with our previous findings ( 16 ).…”
Section: Discussionsupporting
confidence: 93%
“…Given that B-1a–derived natural IgM has anti-inflammatory properties in other inflammatory diseases such as atherosclerosis ( 24 ), we hypothesized that, in addition to IL-10, secretion of IgM by B-1a cells may play a role in IR. Indeed, B-1 cells from obese db / db mice show an impaired IgM response, which may be due to high glucose levels ( 33 ). To explore this, we obtained sIgM null mice whose B cells do not secrete IgM but still express surface IgM and IgD and undergo class switching to express other Ig isotypes ( 34 ), allowing us to study the effect of B cells on IR separately from any effect of IgM.…”
Section: Resultsmentioning
confidence: 99%
“…However, a recent study revealed a link between low levels of peritoneal B-1a cells and low production of IgM in DM mice. 28 Experiments in vitro have confirmed the causal relationship of high concentrations of glucose on reduced secretion of total IgM. 28 Similar mechanisms may work to induce lower s-IgA secretion rates in human DM patients’ salivary glands.…”
Section: Discussionmentioning
confidence: 90%
“… 28 Experiments in vitro have confirmed the causal relationship of high concentrations of glucose on reduced secretion of total IgM. 28 Similar mechanisms may work to induce lower s-IgA secretion rates in human DM patients’ salivary glands. More female participants ( n = 121) were excluded because too little saliva was collected for assay than male participants ( n = 62).…”
Section: Discussionmentioning
confidence: 90%
“…Immunoglobulins production is prototypical function of B cells, and immunoglobulins has important roles in multiple inflammatory diseases including lupus, rheumatoid arthritis and atherosclerosis [12][13][14], and now T2D is also considered as an inflammatory disease [5]. In mice with diabetes, glucose impaired B-1 cell function and the levels of immunoglobulins changed [15]. However, the lack of definitive evidence for an autoimmune component of T2D has limited interest in defining a role for antibodies in T2D.…”
Section: Introductionmentioning
confidence: 99%